On the Performativity of Disinterested Attention for the Experience of Contemporary Art - Natale, Francesca (The Nordic Journal of Aesthetics, 2023)
The aim of this article is to point out that attentional practices don’t simply overlap with control and action/reaction dynamics; they are also strictly connected to non-productivity, non-instrumentality, disinterestedness, contemplation as performative inactivity. Disinterested attention (a definition formulated by Bence Nanay) and free-floating attention help to better understand the apparently seamless and unproblematic transition from passive spectator to active participant/agent of contemporary art. If considering attention in relation to executive functions (planning and organizing our experience in the world we live in) could be persuasive, a self-evident definition of attention strictly considered as “selection for action” is less convincing, and the weakness of this connection becomes clear when goal-oriented attitude is pushed into the background. Attention is often researched into to improve our performances and to overcome the inevitable “blind spots”: experiencing art is about a different way of paying attention, that is fluctuating, “suspended,” fragmented.